2023
DOI: 10.1037/xlm0001153
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in stimulus identification, rule induction, and generalization of learning.

Abstract: In the field of stimulus generalization, an old yet unresolved discussion pertains to what extent stimulus misidentifications contribute to the pattern of conditioned responding. In this article, we perform cluster analysis on six datasets (four published datasets and two unpublished datasets, included N = 950) to examine the relationship between interindividual differences in (a) stimulus identification, (b) patterns of generalized responding, and (c) verbalized generalization rules. The datasets were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The inverse pattern may be observed because of sampling bias where there are far fewer individuals in the first dataset classified to these two groups than in the second (40% versus 72.5%). Regardless of which scale is generally more relevant to the generalization behavior, our results show that the perceptual variability (Figure 1) is one of the contributors to the generalization behavior for some individuals and hence should not be neglected [21][22][23][24][25] .…”
Section: Results Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The inverse pattern may be observed because of sampling bias where there are far fewer individuals in the first dataset classified to these two groups than in the second (40% versus 72.5%). Regardless of which scale is generally more relevant to the generalization behavior, our results show that the perceptual variability (Figure 1) is one of the contributors to the generalization behavior for some individuals and hence should not be neglected [21][22][23][24][25] .…”
Section: Results Discussionmentioning
confidence: 76%
“…Recent research on generalization [21][22][23][24][25] has demonstrated the existence of perceptual variation between and within individuals. Hence, perceptual variation may affect inter-stimulus similarity if perception, rather than physical characteristics, determines the coordinates of stimulus representations in a multidimensional psychological space.…”
Section: Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this work has demonstrated the profound impact of response rules, it failed to identify what caused participants to develop different types of response rules despite similar learning experiences. A recent study found latent group differences in the ability to correctly identify the CS+ (Zaman, Yu, & Lee, 2022). Through cluster analysis, participants allocated to a group with good CS identification performance had a much higher probability of reporting a similarity-based response rule.…”
mentioning
confidence: 99%